Hypokalemia: A Case Report - Susi Setyawati, Kadek; Mansyur, Muh. (Rifa'Institute, 2024)
Hypokalemia occurs when serum potassium levels are lower than normal, it is the most common electrolyte disorder. Especially in hospitalized patients, with a variety of causes and sometimes requiring urgent medical attention. Hypo calcium is usually the result of increased serum potassium excretion or intracellular shift and less commonly due to reduced potassium intake. A 24-year-old woman was admitted to the hospital with complaints of weakness in both lower limbs accompanied by nausea and decreased appetite, which had been felt for 2 days before admission. Previous history of the patient had diarrhea for 4 days, with the consistency of liquid stools, not mixed with mucus and blood. In to make a diagnosis and initiate appropriate therapy, a proper history and examination are necessary. Treatment of hypokalemia is not only aimed at supplementing potassium, but also at identifying the cause. Causes include gastrointestinal loss, intracellular shift, renal potassium loss, and inadequate intake